Consumer product preferences of cultural textile products: co-design with textile artisans from Guatemala and Peru - Engel-Enright, Carol, author; Makela, Carole, advisor; Gloeckner, Gene, advisor; Miller, Nancy, committee member; Dean, Thomas, committee member (Colorado State University. Libraries, 2016)
To view the abstract, please see the full text of the document.